Characterization of the Skin Microbiota of the Cane Toad Rhinella cf. marina in Puerto Rico and Costa Rica - Abarca, Juan G.; Zuniga, Ibrahim; Ortiz-Morales, Gilmary; Lugo, Armando; Viquez-Cervilla, Mariel; Rodriguez-Hernandez, Natalia; Vázquez-Sánchez, Frances; Murillo-Cruz, Catalina; Torres-Rivera, Ernesto A.; Pinto-Tomás, Adrián A.; Godoy-Vitorino, Filipa (Frontiers in Microbiology, 2018)
Rhinella marina is a toad native to South America that has been introduced in the Antilles, likely carrying high loads of microorganisms, potentially impacting local community diversity. The amphibian skin is involved in pathogen defense and its microbiota has been relatively well studied, however, research focusing on the cane toad microbiota is lacking. We hypothesize that the skin microbial communities will differ between toads inhabiting different geographical regions in Central America and the Caribbean. To test our hypothesis, we compared the microbiota of three populations of Rhinella cf. marina toads, two from Costa Rican (native) and one Puerto Rican (exotic) locations. In Costa Rica we collected 11 toads, 7 in Sarapiquí and 4 from Turrialba while in Puerto Rico, 10 animals were collected in Santa Ana. Separate swab samples were collected from the dorsal and ventral sites resulting in 42 samples. We found significant differences in the structure of the microbial communities between Puerto Rico and Costa Rica. We detected as much as 35 different phyla, however communities were dominated by Proteobacteria, Bacteroidetes, Firmicutes and Actinobacteria. Alpha diversity and richness were significantly higher in toads from Puerto Rico and betadiversity revealed significant differences between the microbiota samples from the two countries. At the genus level, we found in Santa Ana, Puerto Rico, a high dominance of Kokuria, Niabella and Rhodobacteraceae, while in Costa Rica we found Halomonas and Pseudomonas in Sarapiquí, and Acinetobacter and Citrobacter in Turrialba. This is the first report of Niabella associated with the amphibian skin. The core microbiome represented 128 OTUs mainly from five genera shared among all samples, which may represent the symbiotic Rhinella’s skin. These results provide insights into the habitat-induced microbial changes facing this amphibian species. The differences in the microbial diversity in Puerto Rican toads compared to those in Costa Rica provides additional evidence of the geographically-induced patterns in the amphibian skin microbiome, and highlight the importance of discussing the microbial tradeoffs in the colonization of new ecosystems.